PERSEPSI MASYARAKAT TERHADAP CALON LEGISLATIF PEREMPUAN PADA PEMILU 2024 DI LOMBOK BARAT - Lalu Silammaulanawa Izzati; Muh. Rizal Hamdi (PRODI HUKUM TATANEGARA, 2025)
This study aims to analyze public perceptions of female legislative candidates in the 2024 General Election (Pemilu) in Electoral District (Dapil) 1 Gerung–Kuripan, West Lombok Regency, and to identify social, cultural, political, and economic factors influencing their electability. This research employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving female legislative candidates, community leaders, election organizers, and residents in the study area. The results indicate that public perception tends to be conservative and gender-biased, with politics still viewed as a male-dominated sphere. Supporting factors include increased education, access to political information, and support from family and social communities. In contrast, inhibiting factors include patriarchal culture, limited structural support from political parties, and low understanding of affirmative policies for female representation. The absence of elected female legislative candidates in the 2024 election demonstrates that the affirmative policies stipulated in Law No. 7 of 2017 and Law No. 2 of 2008 jo. Law No. 2 of 2011 have not been fully effective. The findings of this study are expected to serve as a basis for improving political education and gender awareness at the local level.